Older Adults’ Experience of Meaning at the End of Life in Two Danish Hospices: A Qualitative Interview Study - Viftrup, Dorte Toudal; Prinds, Christina; Nissen, Ricko Damberg; Steenfeldt, Vibeke Østergaard; Søndergaard, Jens; Hvidt, Niels Christian (Frontiers in Psychology, 2021)
The aim of this study was to explore how 10 elderly (>65) patients confronted with imminent death express their thoughts and feelings about death and dying and verbalize meaning as well as discussing how health professionals may better care for patients’ needs for experiencing meaning at the end of life. The study applied a qualitative method with semi-structured interviews with 10 patients at two hospices. The method of analyses was Interpretative Phenomenological Analysis. We found three chronological time themes: 1) Death becoming imminent, 2) Time before dying, and 3) Afterlife. The patients displayed scarce existential vernacular for pursuing meaning with 1) death becoming imminent. They primary applied understandings and vocabulary belonging to a medical paradigm. The patients' descriptions of how they experienced and pursued meaning with 2) time before dying were also predominantly characterized by medical vernacular, but these descriptions did include few existential words and understandings. When expressing thoughts and meaning about 3) afterlife, patients initiated two-ways dialog with the interviewer and primary used existential vernacular. This indicate that the patients’ scarce existential vernacular for talking about meaning is not due to privacy but might be because patients are not used to talking with healthcare professionals about meaning or their thoughts and feelings about death. They were mostly ‘trained’ in medical vernacular. We found that patient’s use of respectively, medical or existential vernacular affect how they experience meaning and hope at the end of life. We encourage health care professionals to enter into existential dialogs with patients to support and strengthen their experiences of meaning and hope at the end of life.